Two islands : Newfoundland and Prince Edward Island - English, Christopher J. B., 1939- (Essays in the history of Canadian law, 2005)
This volume, which includes a number of essays examining women's legal status and access to the courts, is a comprehensive and fascinating examination of legal history in two Canadian provinces.